Sosialisasi dan Pelatihan Smart Farming Bagi Generasi Milenial di Desa Gentungan, Mojogedang, Karanganyar - Emi Widiyanti; Suminah Suminah; Dwiningtyas Padmaningrum (Universitas Sebelas Maret, 2023)
Increasing the Interest of the Gentungan Village Millennial Generation in the Agricultural Sector through Smart Farming Socialization and Training. Gentungan Village, as a pioneer village for organic rice, is currently facing problems in the availability of human resources in the future. This can be seen from the low interest and involvement of young people, especially the millennial generation in Gentungan Village, in the agricultural sector. The purpose of this community service is to increase the interest of the millennial generation in Gentungan Village to engage in the agricultural sector through socialization activities and smart farming training. This service activity was carried out in July - September 2022 involving the active participation of 20 millennial generations in Gentungan Village. This community service activity consists of several activities, namely 1) counseling on the role of youth in agriculture, 2) socialization on smart farming and success stories, 3) training on smart farming and 4) evaluation of the results of socialization and training on smart farming. This community service activity had a positive impact as shown by 90% of participants increasing their knowledge of agriculture 4.0, 60% of participants increasing their knowledge of business opportunities in agriculture 4.0, 15% of participants increasing their positive views of the agricultural sector and increasing participant skills in operating fertilizer drones. This activity also initiated the formation of a group of young farmers Taruna Tani Gentungan Village which in the future is expected to continue agricultural development in Gentungan Village.